Angkutan Kargo Bandara Sentani Jayapura - Siti Masrifah (WARTA ARDHIA, 2010)
Development of cargo especially Jayapura Sentani Airport experiencing a significant increase surely in line with availability of facilities equipment loading and unloading of according to your needs/development of existing cargo and collectors airport (hub) of domestic in the region Papua.This, in its distribution are also experiencing acceleration area smooth, especially on domestic cargo area of Papua. Relative to the like plan or program of airport that will be used as domestic cargo hub Papua them; apron expansion, procurement of cool storage, additional storage of Line I and II, with the assumption that the volume of cargo has increased.